Auditor-Provided Nonaudit Services and Audit Effectiveness and Efficiency: Evidence from Pre- and Post-SOX Audit Report Lags - Knechel, W. Robert; Sharma, Divesh S. (Auditing : a journal of practice and theory, 2012)
The Sarbanes-Oxley Act of 2002 (SOX) effectively bars an auditor from providing nonaudit services to an audit client based on the belief that the resulting economic bonding undermines the auditor's independence and quality of the audit (U.S. House of Representatives 2002). The accounting profession has strongly debated this view and counter-argues that auditor-provided nonaudit services benefit the client. We contribute to this debate by examining the effect of auditor-provided nonaudit services on the effectiveness and efficiency of the audit. We find that higher nonaudit service fees are associated with shorter audit report lags—a potential indicator of audit efficiency—prior to the passage of SOX, but such effects dissipate after SOX. We find that discretionary accruals and financial restatements—potential indicators of audit effectiveness—do not increase when shorter audit lags occur in conjunction with high nonaudit service fees. We also find that the firms with the highest levels of nonaudit service fees prior to SOX have the largest increase in audit lags after SOX. These results suggest that there is some merit to the profession's argument that auditor-provided nonaudit services benefit clients without leading to a loss of audit effectiveness. Data Availability: All data are publicly available from sources identified in the text.